Uma proposta de assinatura digital para imagens por meio de marca d água - Mendes, Fernanda Barbosa Coelho (2008)
Nowadays, digital contents may be shared and easily distributed in Internet, but a lot of intruders use these facilities im order to falsify or illegally distribute this contents. The use of digital watermark is a widely adopted solution, in order to offer security to digital multimedia files by Internet. This solution is adopted with purposes of authentication, copyright and non authorized copy protection. In this dissertation, it is developed a method to construct watermark to assure the authentication and digital sign for digital images. Further, some other requirements may be assisted by this watermark, for example, transparency, public verifying and minimal computer costs. In order to assure transparency, the insertion is made through mapping host image characteristics, by use of wavelet. In order to get a minimal computer costs, it was decided to use lifting scheme instead of filter bank, to implement wavelet transform. To assure watermark public verifying as well security against attacks, it was used hash functions and criptographic algorithms that use non asymmetric or public keys.